2017
DOI: 10.1017/dmp.2016.207
|View full text |Cite
|
Sign up to set email alerts
|

Use of Facial Recognition Software to Identify Disaster Victims With Facial Injuries

Abstract: The present results suggest that the use of this software would provide significant benefit to responders. Although a correct result was returned only 40% of the time, this would still likely represent a benefit for a responder trying to identify hundreds or thousands of victims. (Disaster Med Public Health Preparedness. 2017;11:568-572).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…16 While some of this information may be extremely useful, such as photographs for use with facial recognition software, special framing for these requests may be helpful to encourage guardians to share this particular data. 17,18 Findings from this study indicate that a reunification system needs to clearly delineate with whom the child's personal information will be shared, have clear parameters for the removal of information, and outline the steps used to protect information. Half of the respondents expressed concerns about these topics.…”
Section: Discussionmentioning
confidence: 98%
“…16 While some of this information may be extremely useful, such as photographs for use with facial recognition software, special framing for these requests may be helpful to encourage guardians to share this particular data. 17,18 Findings from this study indicate that a reunification system needs to clearly delineate with whom the child's personal information will be shared, have clear parameters for the removal of information, and outline the steps used to protect information. Half of the respondents expressed concerns about these topics.…”
Section: Discussionmentioning
confidence: 98%
“…We found scarce examples in literature of studies simulating a specific disease-state using techniques such as facial manipulation with moulage or make-up. One other study took photographs of volunteers before and after application of moulage designed to simulate traumatic facial injuries, and found that upon examination of these photographs by a facial analysis software, between 39 and 90% of photographs of injured patients were identified correctly ( 42 ). Clearly, synthetic and augmented datasets have the potential to enable researchers to “tailor” data to a specific context, but their generation and use is not without challenges.…”
Section: Discussionmentioning
confidence: 99%
“…This could save time and money while sparing victims and first responders from the traumatic experience of looking through numerous victim images in search of a "match." 17 According to Frank Hersey's report on biometric update, FRT has been proven helpful for rescuing children from the rubble of the recent earthquake in the southern region of Turkey. 18 The report mentioned that around 144 children have been identified.…”
Section: Disaster Victim Identification/ Examination Of Unidentified ...mentioning
confidence: 99%
“…Due to the availability of powerful facial recognition software, it is possible that commercially accessible technologies can assist disaster responders in successfully reuniting victims with their families by minimizing the number of photos that need to be manually reviewed. This could save time and money while sparing victims and first responders from the traumatic experience of looking through numerous victim images in search of a “match.” 17 According to Frank Hersey's report on biometric update, FRT has been proven helpful for rescuing children from the rubble of the recent earthquake in the southern region of Turkey. 18 The report mentioned that around 144 children have been identified.…”
Section: Applications Of Facial Recognition Technologymentioning
confidence: 99%